A nomogram for predicting upper urinary tract damage risk in children with neurogenic bladder - Li, Qi; Cai, Miao; Pu, Qingsong; Wu, Shengde; Liu, Xing; Lin, Tao; He, Dawei; Wen, Jianguo; Wei, Guanghui (Frontiers in Pediatrics, 2022)
Abstract Purpose: To establish a predictive model for upper urinary tract damage (UUTD) in children with neurogenic bladder (NB) and verify its efficacy. Methods: A retrospective study was conducted that consisted of a training cohort with 167 NB patients and a validation cohort with 100 NB children. The clinical data of the two groups were compared first, and then univariate and multivariate logistic regression analyses were performed on the training cohort to identify predictors and develop the nomogram. The accuracy and clinical usefulness of the nomogram were verified by receiver operating characteristic (ROC) curve, calibration curve and decision curve analyses. Results: There were no significant differences in other parameters between the training and validation cohorts except for age (all P > 0.05). Recurrent urinary tract infection, bladder compliance, detrusor leak point pressure, overactive bladder and clean intermittent catheterization were identified as predictors and assembled into the nomogram. The nomogram showed good discrimination with the area under the ROC curve (AUC) in the training cohort (0.806, 95% CI: 0.737-0.874) and validation cohort (0.831, 95% CI: 0.753-0.0.909). The calibration curve showed that the nomograms were well calibrated, with no significant difference between the predicted and observed probabilities. Decision curve analysis indicated that the nomogram has good clinical applicability. Conclusion: This study presents an effective nomogram incorporating five clinical characteristics that can be conveniently applied to assess NB children' risk of progressing to UUTD.